Phylogenetic positions of seven poorly known species of Ferula (Apiaceae) with remarks on the phylogenetic utility of the plastid trnH-psbA, trnS-trnG, and atpB-rbcL intergenic spacers. Issue 5 (4th July 2018) - Piwczyński, Marcin; Wyborska, Dominika; Gołębiewska, Joanna; Puchałka, Radosław
Abstract : Ferula L. is one of the most species-rich and taxonomically difficult genera of Apiaceae. In this study, we obtained nrDNA ITS sequences of seven poorly known species of Ferula ( Ferula anatolica, Ferula sp. (tentatively identified as F. candelabrum by collectors), F. drudeana, F. huber-morathii, F. marmarica, F. talassica, and F. tunetana ) and explored their phylogenetic positions using 148 ITS sequences of the subtribe Ferulinae from GenBank. Five of these newly sequenced species fall into three groups, corresponding to clades recognized in earlier molecular studies. Ferula sp. are added to clade, which is mostly composed of Central Asian species. This placement showed that identification as F. candelabrum was erroneous. The second clade, which is mostly composed of Mediterranean taxa, includes two species from North Africa: F. marmarica and F. tunetana . Despite the well-supported monophyly of this clade, the relationships inside this group need to be revised, as broadly distributed F. communis is paraphyletic with respect to other species. Ferula drudeana and F. huber-morathii, two narrow endemics from Turkey, are placed in the Central Asian clade. Two species, F. anatolica and F. talassica, do not fall into any of the recognized clades. In addition, we examined the sequence variation of three potentially highly variable pDNA regions, the trnH-psbA, trnS-trnG, and atpB-rbcL intergenic spacers, for a subset of 18 specimens. The resulting pDNA and ITS based phylogenetic trees were incongruent, as supported by significant ILD tests. The cause of this incongruence can be manifold, including hybridization, a lack of a phylogenetic signal, and homoplastic substitutions. Our analyses suggest that only trnS-trnG can be added to the list of pDNA markers used for phylogenetic studies of Ferula, as it has the highest number of parsimony informative characters and is easy to amplify from degraded material.